Small calcified lesions suggestive of neurocysticercosis are associated with mesial temporal sclerosis - Marcos C. B. Oliveira; Maria G. M. Martin; Miriam H. Tsunemi; Gilson Vieira; Luiz H. M. Castro (Arquivos de Neuro-Psiquiatria, 2014)
Recent studies have suggested a possible relationship between temporal lobe epilepsy with mesial temporal sclerosis (MTS) and neurocysticercosis (NC). We performed a case-control study to evaluate the association of NC and MTS. Method: We randomly selected patients with different epilepsy types, including: MTS, primary generalized epilepsy (PGE) and focal symptomatic epilepsy (FSE). Patients underwent a structured interview, followed by head computed tomography (CT). A neuroradiologist evaluated the scan for presence of calcified lesions suggestive of NC. CT results were matched with patients’ data. Results: More patients in the MTS group displayed calcified lesions suggestive of NC than patients in the other groups (p=0.002). On multivariate analysis, MTS was found to be an independent predictor of one or more calcified NC lesions (p=0.033). Conclusion: After controlling for confounding factors, we found an independent association between NC calcified lesions and MTS.